Restoration ecology of coastal lagoons: new methods for the prediction of ecological trajectories and economic valuation. Issue 1 (19th October 2015) - De Wit, Rutger; Rey‐Valette, Helene; Balavoine, Juliette; Ouisse, Vincent; Lifran, Robert
Abstract: Conservation of the seven lagoons of the Palavas complex (southern France) has been severely impaired by nutrient over‐enrichment during at least four decades. The effluents of the Montpellier wastewater treatment plant (WWTP) represented the main nutrient input. To improve the water quality of these lagoons, this WWTP was renovated and upgraded and, since the end of 2005, its effluents have been discharged 11 km offshore into the Mediterranean (total investment €150 M). Possibilities of ecosystem restoration as part of a conservation programme were explored by a focus group of experts. Their tasks were: (i) to evaluate the impact of the reduction of the nutrient input; (ii) if necessary, to design additional measures for an active restoration programme; and (iii) to predict ecosystem trajectories for the different cases. Extension of Magnoliophyta meadows can be taken as a proxy for ecosystem restoration as they favour the increase of several fish (seahorse) and bird (ducks, swans, herons) species, albeit they represent a trade‐off for greater flamingos. Additional measures for active ecosystem restoration were only recommended for the most impaired lagoon Méjean, while the least impaired lagoon Ingril is already on a trajectory of spontaneous recovery. A multiple contingent valuation considering four different management options for the Méjean lagoon was used in a pilot study based on face‐to‐face interviews with 159 respondents. Three levels of ecosystem restoration were expressed in terms of recovery of Magnoliophyta meadows, including their impact on emblematic fish and avifauna. These were combined with different options for access (status quo, increasing access, increasing access with measures to reduce disturbance). The results show a willingness of local populations to pay per year about €25 for the highest level of ecological restoration, while they were only willing to allocate about €5 for additional footpaths and hides. Copyright © 2015 John Wiley & Sons, Ltd.